Meningkatkan Aktivitas dan Hasil Belajar Pendidikan Agama Hindu dengan Penerapan Metode Resitasi Siswa Kelas IV SD Negeri 25 Cakranegara - Dewi, Ni Kadek (ARZUSIN, 2022)
This study aims to determine the increase in activities and learning outcomes of Hindu religious education through the application of the Recitation method in Class IV SD Negeri 25 Cakranegara in the academic year 2021/2022. This research is a classroom action research designed in two cycles and each cycle consists of four stages, namely planning, action, observation, and reflection. The subjects of this study were fourth grade students of SD Negeri 25 Cakranegara, totaling 12 students. Data collection methods used in this study are observation, interviews, assignments, and documents. Analysis of student activity data obtained from observations during the implementation of corrective actions. Analysis of student learning outcomes obtained from the average value of student assignments. The results of this study indicate that the application of the recitation method in the learning process can increase student learning activities from low criteria with 62.29% completeness to medium criteria with 78.57% completeness in cycle I. In cycle II it increases again from 59% completeness with moderate criteria. to 100% with high criteria. Likewise, student learning outcomes also experienced an increase, in conditions before the action with a percentage of 66.67% and in the first cycle it was included in the sufficient category with a percentage of 83.33%. Then for the evaluation results in the second cycle, the students' completeness scores increased to 100%. So the learning outcomes of fourth grade PAH subjects at SD Negeri 25 Cakranegara can be improved by applying the Recitation method.